A prática clínica em terapia ocupacional focada em cinesioatividade e treino de AVD favorece a recuperação de independência em paciente com acidente vascular encefálico - LOBO, Denis Carvalho (2023)
OBJECTIVES: To present evidence on the efficacy of specific approaches to Occupational Therapy such as Activities of Daily Living (ADL) and Kinesioactivity with a stroke survivor patient. SEARCH METHODS: This is a study quantitative in the unique case, whose selected individual manifests hemiparesis in the left side triggered by ischemic brain event, has as main complaint not being able to perform the basic activities independently and the difficulty of locomotion. The evaluation instruments used were: anamnesis, the FIM, The MiniMental State Examination, the pain (Visual analogue scale), muscular force (MRC) and monofilaments of Semmes Weinstein (MSW). The procedures were recorded in sessions between ADL and Kinesioactivity. The data generated were plotted in the GraphPad, Prism 6.0 to perform descriptive statistics using the Analysis of Variance (ANOVA), Tukey p <0.05. The graphic were edited in columns to display Mean ± Standard Deviation. MAIN RESULTS: Kinesioactivity and training of ADL favored the recovery of functional status given by FIM (Right, 7.0 ± 0.0; Outpatient, 6.26 ± 1.19 p> 0.05). The results found in the MRC revealed that the gain in the degree of muscle strength occurred in every affected body, with no statistically difference between the upper and lower limbs (Right, 4.71 ± 0.35, Outpatient, 4.43 ±, 53 p > 0.05). The tactile sensitivity of the affected hand responded positively to the treatment, to the point that there was no statistical significance between the right and left hand sensitivities (Right, 0.62 ± 86, Outpatient, 2.4 ± 0.89 p > 0.05). However, there were no alterations in the general state of pain manifestation in the patient's body, and data on range of motion did not show gains. CONCLUSIONS: The ADL and Kinesioactivity in neurological rehabilitation were effective in the study to minimize disabilities, above all by stimulating and developing of the Occupational Performance. The findings presented here still lack deepening regarding, for example, the percentage contribution of each approach to patient recovery. But it corroborates with publications that demonstrate the effectiveness of specific interventions of Occupational Therapy in Rehabilitation Sciences.